Effects of condensed tannin on in vitro ruminal fermentation - McKiearnan, Allison Nicole (Kansas State University, 2015)
Condensed tannins (CT) in plants are phenolic compounds with relatively high binding affinities for proteins. In ruminants, dietary CT limit DM intake and digestibility, and ruminal protein degradation by forming CT-protein complexes. Effects of dietary CT, animal species, prior dietary CT exposure, and antimicrobial inclusion on 48-h rate and extent of digestion were measured in two in vitro experiments. Cattle, sheep, and goats (n = 3 / species) were used in a 2-period, randomized complete-block experiment with a 2 × 3 × 2 × 3 factorial arrangement of treatments. Factor 1 was substrate: tannin-free or high-CT. Factor 2 was source of ruminal fluid inoculum: cattle, sheep, or goat. Factor 3 was prior animal exposure to a high-CT diet: non-exposed or exposed. Factor 4 was inclusion of antimicrobials: no antimicrobial, penicillin + streptomycin to suppress bacterial activity, or cycloheximide to suppress fungal activity in the fermentation. Tannin-free or high-CT substrates were incubated in vitro using ruminal fluid from animals either not exposed (period 1) or exposed to dietary CT (period 2). Periods consisted of an adaptation to tannin-free (10 d) or high-CT diets (21 d) and a 15-d period of ruminal-fluid collection via stomach tube. The presence of CT or penicillin + streptomycin in in vitro fermentation reduced (P < 0.001) total gas pressure, DM disappearance, and total VFA, acetate, propionate, butyrate, valerate, and branched-chain VFA concentrations. We concluded that: 1) CT had negative effects on fermentation, 2) prior exposure to dietary CT attenuated some but not all negative effects, and 3) CT effects were similar to the effects of penicillin + streptomycin.
Keywords: condensed tannins; dietary tannin adaptation; in vitro fermentation; Animal Sciences (0475); Biology, Animal Physiology (0433); Chemistry, Agricultural (0749); Toxicology (0383)